Anticoagulation and Mortality Rates among Hospitalized Patients with Atrial Fibrillation - Piazza, Gregory; Hurwitz, Shelley; Harrigan, Lindsay M.; Jenkins, Kathryn L.; Hohlfelder, Benjamin; Fanikos, John; Goldhaber, Samuel Z. (TH Open, 2018)
Atrial fibrillation (AF) is associated with an increased rate of mortality, heart failure, and stroke. We conducted an observational study to assess the relationship between anticoagulation and adverse clinical outcomes in hospitalized patients with AF. We performed a 5,000-consecutive-patient retrospective cohort analysis of anticoagulation prescription and 90-day outcomes in patients with AF hospitalized at Brigham and Women's Hospital from May 2008 to September 2014. All-cause mortality at 90 days was 5.4%. The frequency of death between hospital discharge and day 90 was lower in patients who were anticoagulated at discharge (2.8 vs. 7.1%, p < 0.001). Anticoagulation prescription at discharge was associated with a 60% reduction in death between discharge and day 90, after adjustment for confounding factors. Major adverse events at day 90, including death, myocardial infarction, stroke, and major bleeding, were more frequent in patients who were not prescribed anticoagulation at discharge (16.5 vs. 10.4%, p < 0.001). In multivariable regression analysis, prescription of anticoagulation at discharge predicted a lower mortality (adjusted odds ratio (OR), 0.4; 95% confidence interval (CI), 0.3–0.53) and lower major adverse event rate (adjusted OR, 0.64; 95% CI, 0.54–0.76) by day 90. In conclusion, all-cause mortality at 90 days was high among inpatients with AF. Patients with AF who were not prescribed anticoagulation at discharge had an increased risk of death at 90 days. Hospitalization represents a special opportunity to optimize cardiovascular risk reduction strategies, including anticoagulation.
Keywords: anticoagulation; atrial fibrillation; mortality; adverse events